Succeeding as an international student in the United States and Canada - Bhandari, Amrita (Journal of International Students, 2012)
In Succeeding as an International Student in the United States and Canada, the author, Charles Lipson, provides an informative guide to campus life for both undergraduate and graduate foreign students who are interested in pursuing their studies for the first time in the institutions of higher education in the United States and Canada. His intention is that this book can serve as “a friendly, informative guide, one that helps you succeed in your classes, labs, and everyday activities” (p. xvi).